2021
DOI: 10.1093/europace/euab164
|View full text |Cite
|
Sign up to set email alerts
|

The V6-V1 interpeak interval: a novel criterion for the diagnosis of left bundle branch capture

Abstract: Aims We hypothesized that during left bundle branch (LBB) area pacing, the various possible combinations of direct capture/non-capture of the septal myocardium and the LBB result in distinct patterns of right and left ventricular activation. This could translate into different combinations of R-wave peak time (RWPT) in V1 and V6. Consequently, the V6-V1 interpeak interval could differentiate the three types of LBB area capture: non-selective (ns-)LBB, selective (s-)LBB, and left ventricular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
113
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(123 citation statements)
references
References 8 publications
5
113
0
5
Order By: Relevance
“…Left ventricular activation time (LVAT) was calculated from QRS onset to the R wave peak in lead V6 (V6RWPT) ( 26 , 28 ). The interval between the R wave peak time in V6 and V1 was defined as the V6–V1 interpeak interval (V6V1 IPI) and used as an estimation of interventricular electrical dyssynchrony ( 29 ).…”
Section: Methodsmentioning
confidence: 99%
“…Left ventricular activation time (LVAT) was calculated from QRS onset to the R wave peak in lead V6 (V6RWPT) ( 26 , 28 ). The interval between the R wave peak time in V6 and V1 was defined as the V6–V1 interpeak interval (V6V1 IPI) and used as an estimation of interventricular electrical dyssynchrony ( 29 ).…”
Section: Methodsmentioning
confidence: 99%
“…In this case, dynamic QRS morphologic changes served as a criterion for the LBB capture diagnostic. 4 When the QRS morphology changed and the stimulus-to–left ventricle activation time (Stim-LVAT) was decreased by ≥10 ms, 2 it was confirmed that left ventricular septum pacing changed to nonselective LBBP. This means that activation of the myocardium was achieved in addition to LBB.…”
Section: Case Reportmentioning
confidence: 96%
“…Meanwhile, several groups have been working on the establishment of novel evidence based, rather than arbitrary, criteria for differentiation between LBBP and LV septal pacing. [33][34][35] Although, all echocardiograms were analyzed anonymized, at random, and after the last patient ended follow-up, it cannot be fully excluded that outcomes may have been biased since pacing leads in the interventricular septum were often easily visible.…”
Section: Future Perspectives and Study Limitationsmentioning
confidence: 99%
“…On the other hand, patients might have been classified as “successful attempt” in whom deep LV septal pacing (with secondary activation of the left sided Purkinje system) was performed instead of direct capture of the LBB. Meanwhile, several groups have been working on the establishment of novel evidence based, rather than arbitrary, criteria for differentiation between LBBP and LV septal pacing 33–35 …”
Section: Future Perspectives and Study Limitationsmentioning
confidence: 99%